Role of excipients and polymeric advancements in preparation of floating drug delivery systems - Kaushik, Avinash Y (Int J Pharm Investig, 2015)
Since decade or two, the development of floating drug delivery systems becomes a significant and novel tool as having low density than gastric content. There are various advanced polymers including chitosan, eudragit, etc., and excipients such as; pore forming agent, surfactants, etc. All of them are discussed briefly, and results are concluded from various reputed researches. We have discussed all natural and synthetic systems with their effect on the release and other parameters which are essential for the floating formulation development.